Applicability of nutrition assessment methodologies in post-disaster situations in five typhoon affected Philippine provinces (2009)
This study assessed the applicability of the different nutrition assessment methodologies, namely, anthropometry, clinical assessment, focus group discussion, and key informant interview in five disaster affected provinces in the Bicol and MIMAROPA regions. It also described the nutrition situation and generated implications on the use of these methodologies as inputs in the development of a protocol for rapid nutrition assessment in post-disaster situations. The study covered a total of 500 randomly selected households. The applicability of methodologies was assessed using statistical tests and evaluated using the following criteria: ease of use, appropriateness, time requirement, subject-friendliness, and ease of interpretation. Results showed that undernutrition was found to be a problem among preschool and older children, adults, and the elderly. Common illnesses such as fever, cold, and coughs were also observed including signs suggestive of micronutrient malnutrition. Results of the focus group discussion and key informant interviews showed that the primary causes of undernutrition are inadequate food intake and poor health status. The study recommends the use of mid-upper arm circumference measurements, weighing using calibrated bathroom scale, clinical assessment, and key informant interviews as methodologies for inclusion in the protocol for rapid nutritional assessment.
Keywords: Disaster victims -- Nutrition -- Evaluation